2005
DOI: 10.1039/b505605e
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopic investigations of supersaturated NaClO4 aerosols

Abstract: Supersaturated NaClO4 aerosols have been studied using a Fourier transform infrared (FTIR) spectrometer coupled with an aerosol flow tube (AFT). Compared with previous Raman results, the water O-H stretching envelope in the supersaturated solutions of NaClO4 aerosols was more structured in response to changing RH, revealing at the same time the existence of water monomers weakly hydrogen-bonded with ClO4- at extremely high concentrations. Due to enhanced ion interactions in the supersaturated solutions of NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
(138 reference statements)
4
27
1
Order By: Relevance
“…Previous studies suggested that supersaturated NaClO 4 aerosols effloresced at ~10% RH to form metastable anhydrous particles [5,6] . Therefore, their morphologic changes at ~10% attracted special attention in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that supersaturated NaClO 4 aerosols effloresced at ~10% RH to form metastable anhydrous particles [5,6] . Therefore, their morphologic changes at ~10% attracted special attention in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Under the supersaturated state, crystallization of aerosol droplets is mainly affected by kinetic factors, resulting in metastable solids instead of thermodynamically stable ones [2][3][4] . It was found that supersaturated NaClO 4 aerosol droplets were crystallized to form metastable anhydrous particles at ~10% relative humidity (RH) rather than NaClO 4 ·H 2 O with an equilibrium RH of ~40% [5,6] . The crystallization of supersaturated aerosols and the formation of metastable solids are the two fundamental problems of crystallography and atmospheric sciences [5][6][7][8][9][10][11][12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For an isolated ClO 4 – anion all these four modes are RS active and ν 3 and ν 4 are IR active only. However, when the high symmetry structure of the ClO 4 – anions is even slightly perturbed, then its degenerated vibrational modes may split and some of the inactive modes may become active …”
Section: Resultsmentioning
confidence: 99%
“…The assignments of these vibrations were proposed by comparing their frequencies with the literature data for several similar ionic amminemetal(II) complexes [7][8][9]. All characteristic bands frequencies of the internal vibrations of NH 3 perturbed somehow, its degenerated vibrational modes may split and some of the inactive modes may be activated [10,11]. The proton-weighted phonon density of states function G( ) was calculated according to the formula (1) for double differential crosssection of neutrons scattered on protons in the sample [12]:…”
Section: Vibrational Spectrummentioning
confidence: 99%